Hadi Mulyadi's Thought Construction on the Evaluation of Education Policy in East Kalimantan: A Study of the Integration of the Roles of Academics and Politicians in Regional Leadership - Dewi Mawarni; Rizky Firnanda (Al-Ilmu, 2026)
This study is a figure-based research examining the construction of Hadi Mulyadi's thought in the evaluation of education policy in Indonesia, with a focus on the integration of academic, political, and regional leadership roles during his tenure as Vice Governor of East Kalimantan (2018–2023). The background of this research lies in the uniqueness of Hadi Mulyadi's profile, which combines extensive academic experience in higher education, professional management practice, and political–bureaucratic leadership at the regional level. The objective of this study is to analyze how Hadi Mulyadi's perspectives and practices in education policy evaluation can be understood through public policy and governance frameworks. This research employs a qualitative approach with a figure study design. Data were collected through in-depth interviews, document analysis, and policy review, and were analyzed using thematic analysis. The findings indicate that Hadi Mulyadi's evaluation of education policy aligns with William N. Dunn's policy evaluation criteria, particularly effectiveness, equity, responsiveness, and appropriateness, as reflected in regional scholarship programs, expanded access to education, and support for non-civil servant teachers and religious education. These policies also reflect Human Capital Theory, viewing education as a strategic investment to prepare local human resources in East Kalimantan for the development of Indonesia's new capital city (IKN). The integration of academic and political roles can be explained through the Multiple Streams Framework, while policy effectiveness is evident through the Context, Input, Process, and Product (CIPP) evaluation model. This study concludes that Hadi Mulyadi's leadership demonstrates a contextual, decentralized, and good governance–oriented approach to education policy evaluation